Information literacy and final year trainee teachers: perceptions and practices of the research process / Siri Sena Baba Hamid - Baba Hamid, Siri Sena (Institute of Graduate Studies, UiTM, 2016)
The case study discovers with certainty about information literacy competencies in carrying out research process among trainees of the Malaysian Teacher Education Institute within the five northern region campuses. The Institute has a mission through its dynamic teacher training programmes to produce 21st century world-class trained teachers competent in research skills. In doing so, it is highly important to see that these trainees have acquired a comprehensive understanding of information literacy in their research process. Yet, it is a pivotal fact indicated by recent researchers that most future teachers often enter teaching without the necessary information literacy skills and knowledge in research process. An Information Literacy Research Process Model (ILRPM) is developed to explain the trainees’ behaviour of information literacy seeking skills in accessing, evaluating and applying their needed information when conducting their research process. The scope of study is based on full-time final year undergraduate trainee teachers for the Educational Degree Programme in Kedah, Perlis and Penang, who are required to conduct their school based action research final project paper. The population is segregated into science and non-science from various teacher education content-area specializations. The study uses an indepth triangulation analysis to investigate information literacy competency problems and issues faced by the trainee teachers in doing their research process…